STRATEGI PENANAMAN MODAL ASING (PMA) PT PERTAMINA LUBRICANTS DI THAILAND TAHUN 2015 - Ardi, Andre; Satria, Aldi (Moestopo Journal of International Relations (MJIR), 2024)
The purpose of this research is to analyze the Foreign Direct Investment (FDI) strategy of PT Pertamina Lubricants in Thailand in 2015. The method used in this research is qualitative with descriptive research type, the data collection techniques used include interviews, official documents, literature books, journals, reports, and online sources. The theories or concepts utilized in this study include foreign direct investment, multinational corporations, business strategy, competitive strategy, and political strategy. The results of this study explain that PT Pertamina Lubricants adopted business, competitive, and political strategies, with acquisition being the most effective method for entering the Thailand market. Several factors influenced this investment decision, including government regulations, market competition, and tax policies. The acquisition strategy enabled PT Pertamina Lubricants to establish a stronger market presence, leverage existing distribution networks, and enhance competitive advantages. This study provides insights into how multinational corporations strategize their foreign investments, particularly in Southeast Asia.